Response of fabricated germanium optical fibre subjected to low dose neutron-gamma irradiation - Mustafa, Salasiah; Ahmad Saad, Fathinul Fikri; Tamchek, Nizam; Mohamed, Faizal; Bajuri, Farid; Mohd Noor, Noramaliza (UniMAP PRESS, 2018)
The main purpose of this study is to establish the thermoluminescence response (TL) of fabricated 6% mol Ge-doped optical fibre towards a low dose neutron-gamma irradiation which includes dose linearity, fading signal, minimum detectable dose(MDD) and glow curve analysis. A cylindrical optical fibre with outer diameter of (604 μm and 483 μm) and flat optical fibres with outer dimension of 620x 165μm were employed in this study. All fibres were exposed with mixed neutron-gamma radiation that emitted from a 241Am–Be radiation sourcelocated at Neutron Laboratory, Nuclear Science Building, Universiti Kebangsaan Malaysia for 5-, 7-, 14-, 21-, and 28 days. The source to the sample distance was set at 5 cm. For fading effect, the samples were kept at room temperature and read-out up to 71days’ post-irradiation. The glow curve and the minimum detectable dose were evaluated using the glow curve which was plotted using Microsoft Excel software and alsocorresponded with the formulafound inFuretta et al.(2001). All the fabricated optical fibres showeda dose linearity response for a range of dose given at 30, 50, 101, 151 and 201 mGy. The minimum detectable dose for 604 μm and 483 μm cylindrical optical fibre was0.25 mGy and 0.42 mGy. Meanwhile,for 620 μm flat optical fibre, the detectable dose was1.13mGy. At 71days’ post-irradiation, all the fibres showedless than 30% of signal fading. Moreover, single broad peak can be found for cylindrical fibre and double peak for flat fibre. These result show that fabricated Germanium optical fibre givesa good response to a low dose mixed gamma -neutron irradiation.